Aberrant breast tissue in complete androgen insensitivity syndrome. (1st February 2018) - Nazzaro, G.; Genovese, G.; Brena, M.; Passoni, E.; Tadini, G.
Abstract : Clickhere for the corresponding questions to this CME article.